The Comparison of Blood Glucose Check Results Using Photometer and Glucometer - Iswarno; Retno Sulistiyowati; Kurnia Ritma Dhanti; Tantri Analisawati (Institute of Computer Science (IOCS), 2022)
Diabetes mellitus is a disease caused by high blood glucose levels. Blood glucose is a sugar that functions as an energy source for humans, formed from carbohydrates consumed and then stored as glycogen in the liver and muscles. Examining blood glucose levels can be done in two ways, namely using a photometer and a glucometer. This study aimed to determine differences in the results of blood glucose checks measured using a photometer and glucometer. The research was conducted with an analytic observational design with a cross-sectional approach. The study was conducted in June 2022. The population in this study were all Prolanis participants at the Klirong 1 Public Health Care Center. The sampling technique in this study used the accidental sampling technique. The data analysis used paired sample T-test. The results of the blood glucose checks using a photometer and glucometer showed a p-value (0.000) and alpha value (0.05). So it can be concluded that there is a significant difference between the results of blood glucose checks using a photometer and a glucometer.